2021
DOI: 10.3390/cancers13133227
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxychloroquine (HCQ) Modulates Autophagy and Oxidative DNA Damage Stress in Hepatocellular Carcinoma to Overcome Sorafenib Resistance via TLR9/SOD1/hsa-miR-30a-5p/Beclin-1 Axis

Abstract: Sorafenib is used for treating advanced hepatocellular carcinoma (HCC), but some patients acquire sorafenib resistance. We investigated the mechanisms underlying acquired sorafenib resistance in HCC cells and targeted them to re-sensitize them to sorafenib. In silico analysis indicated that toll-like receptor (TLR)-9 was significantly overexpressed, and that miRNA (hsa-miR-30a-5p) was downregulated in sorafenib-resistant HCC cells, which modulated HCC cell proliferation, oxidative stress, and apoptosis. TLR9 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 61 publications
(92 reference statements)
2
19
0
Order By: Relevance
“…Therefore, we can conclude that instead of an anti-tumor role, autophagy is playing a cytoprotective action in our sorafenib-resistant HCC in vitro models that permits sorafenib-mediated cell death evasion. These findings are also supported by a study where administration of hydroxychloroquine modulates autophagy and oxidative stress to surpass sorafenib resistance in Huh7 cells displaying a resistant phenotype [50]. Similarly, chloroquine promoted the anti-tumor effect of sorafenib in vitro and in vivo [51]; while a combination of sorafenib plus 3-methyladenine, an inhibitor of autophagy at early phases, also enhanced the apoptotic rate in HCC [52].…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, we can conclude that instead of an anti-tumor role, autophagy is playing a cytoprotective action in our sorafenib-resistant HCC in vitro models that permits sorafenib-mediated cell death evasion. These findings are also supported by a study where administration of hydroxychloroquine modulates autophagy and oxidative stress to surpass sorafenib resistance in Huh7 cells displaying a resistant phenotype [50]. Similarly, chloroquine promoted the anti-tumor effect of sorafenib in vitro and in vivo [51]; while a combination of sorafenib plus 3-methyladenine, an inhibitor of autophagy at early phases, also enhanced the apoptotic rate in HCC [52].…”
Section: Discussionmentioning
confidence: 59%
“…Hydroxychloroquine has been reported to induce oxidative DNA damage in mouse embryonic fibroblasts and human hepatocellular carcinoma cells ( Besaratinia et al, 2021 ; Chen et al, 2021 ). We aimed to evaluate the oxidative stress status of pterygium and conjunctival cells after hydroxychloroquine treatment by determining the expression of SOD2 (an oxidative stress marker ( Yang et al, 2019b ); and the cellular ROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxychloroquine would induce cellular oxidative stress ( Besaratinia et al, 2021 ; Chen et al, 2021 ). We confirmed that hydroxychloroquine could increase cellular ROS level ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Wnt/β-catenin pathway plays an important role in human CRC tumorigenesis [83]. Moreover, our very recent study identified that FABP6 is the Wnt signaling pathway molecule which may indirectly interact with β-catenin [84]. Therefore, the correlations among FABP6, miR-320, and the Wnt/β-catenin pathway in CRC need to be further explored.…”
Section: Discussionmentioning
confidence: 99%